Synthesis of Ru alkylidene complexes - Kadyrov, Renat; Rosiak, Anna (Beilstein Journal of Organic Chemistry, 2011)
The present work describes the robust synthesis of Ru alkylidene complexes (PCy3)2Cl2Ru=CHR – precursors for metathesis catalysts. Moreover, the dynamic behavior of complexes where R = 2-naphthyl and 2-thienyl was studied. 1H NMR techniques were employed to establish the preferred conformations in solution for both complexes and the energy barrier for rotation around single (Ru=)CH–C(thienyl) bond was estimated (ΔG≠303K = 12.6 kcal/mol).
Keywords: alkylidene complexes; metathesis; rotation barrier; ruthenium

(untitled) - Weskamp, T.; Schattenmann, W. C.; Spiegler, M.; Herrmann, W. A. (Angew. Chem., 1998)
Angew. Chem. Int. Ed. 1998, 37, 2490–2493.

(untitled) - Diesendruck, C. E.; Tzur, E.; Lemcoff, N. G. (Eur. J. Inorg. Chem., 2009)

(untitled) - Samojłowicz, C.; Bieniek, M.; Grela, K. (Chem. Rev., 2009)

(untitled) - Vougioukalakis, G. C.; Grubbs, R. H. (Chem. Rev., 2010)

(untitled) - Schwab, P.; Grubbs, R. H.; Ziller, J. W. (J. Am. Chem. Soc., 1996)

(untitled) - Wilhelm, T. E.; Belderrain, T. R.; Brown, S. N.; Grubbs, R. H. (Organometallics, 1997)

(untitled) - Grünwald, C.; Gevert, O.; Wolf, J.; González-Herrero, P.; Werner, H. (Organometallics, 1996)

(untitled) - van der Schaaf, P. A.; Kolly, R.; Hafner, A. (Chem. Commun., 2000)

(untitled) - van der Schaaf, P. A.; Kolly, R.; Kirner, H.-J.; Rime, F.; Mühlebach, A.; Hafner, A. (J. Organomet. Chem., 2000)

(untitled) - Wolf, J.; Stüer, W.; Grünwald, C.; Werner, H.; Schwab, P.; Schulz, M. (Angew. Chem., Int. Ed., 1998)
Angew. Chem. 1998, 110, 1165–1167.

(untitled) - Sebbar, N.; Bockhorn, H.; Bozzelli, J. W. (J. Phys. Chem. A, 2005)

(untitled) - Head-Gordon, M.; Pople, J. A. (J. Phys. Chem., 1993)

(untitled) - Grajcar, L.; Baudet, J. (J. Mol. Struct., 1977)

(untitled) - Parr, W. J. E.; Wasylishen, R. E.; Schaefer, T. (Can. J. Chem., 1976)

(untitled) - Tobrman, T.; Meca, L.; Dvořáková, H.; Černý, J.; Dvořák, D. (Organometallics, 2006)

(untitled) - Schmidt, U.; Werner, J. (Synthesis, 1986)

(untitled) - Herz, W.; Juo, R.-R. (J. Org. Chem., 1985)

(untitled) - Paquette, L. A.; Gugelchuk, M.; McLaughlin, M. L. (J. Org. Chem., 1987)

(untitled) - Katayama, H.; Ozawa, F. (Organometallics, 1998)